Meat Alternatives and Their Impact on Human Health: A Comprehensive Review - Antonella Dalle Zotte; Emanuele Pontalti; Marco Cullere (Meat and Muscle Biology)
In the contemporary landscape, conventional meat faces increasing scrutiny due to recent allegations raised by various associations and scientific groups. While these criticisms are often linked to excessive meat consumption, a growing number of individuals are reducing or eliminating meat from their diets, questioning its role in a healthy diet. The consequent request for alternative protein sources has prompted the food industry to create so-called “meat alternatives” products. These emerging foods aim to replicate the sensory characteristics of conventional meat, eliminating the need to slaughter animals, and minimize environmental impact. Despite the misleading claims of various supporters, the long-term nutritional sustainability of these novel products remains unclear. To date, products resembling meat, which exploit different sources such as plants, algae, fungi, insects, and in vitro–cultured animal cells (cell-based food) require an unavoidable level of industrial processing, rendering the final products as ultra-processed foods (UPF). Given the well-established adverse effects associated with prolonged consumption of UPF, it raises questions about whether these products truly serve as a viable substitute for whole and unprocessed foods, like meat. With limited scientific knowledge and technological innovation to date, the long-term effects of meat alternatives on human health remain unclear. Addressing this crucial gap, together with guaranteeing transparency of research, should be a top priority for the food industry, guiding decisions on whether investment in these emerging food products is not only a cost-effective but also a health-conscious strategy.